Desert solitaire eaudiobook A season in the wilderness. - Abbey, Edward (Tantor Media, 2011)
When Desert Solitaire was first published in 1968, it became the focus of a nationwide cult. Rude and sensitive. Thought-provoking and mystical. Angry and loving. Both Abbey and this book are all of these and more. Here, the legendary author of The Monkey Wrench Gang, Abbey's Road, and many other critically acclaimed books vividly captures the essence of his life during three seasons as a park ranger in southeastern Utah. This is a rare view of a quest to experience nature in its purest form—the silence, the struggle, the overwhelming beauty. But this is also the gripping, anguished cry of a man of character who challenges the growing exploitation of the wilderness by oil and mining interests, as well as by the tourist industry. Abbey's observations and challenges remain as relevant now as the day he wrote them. Today, Desert Solitaire asks if any of our incalculable natural treasures can be saved before the bulldozers strike again.